Hubungan Sosio Demografi dengan Kejadian Stunting pada Balita di Puskesmas Perawatan Tanoh Alas Kabupaten Aceh Tenggara - Siti Aminah; Basri Aramico Ib; Nopa Arlianti (CV. ALIM'SPUBLISHING, 2026)
Stunting is a major indicator of chronic nutritional problems that affect children’s growth and development. In Indonesia, stunting prevalence remains high and is a national public health concern. This study aimed to analyze the relationship between socio-demographic factors and stunting incidence among toddlers in the working area of the Tanoh Alas Health Center, Southeast Aceh Regency, in 2025. This study used an analytical quantitative design with a cross-sectional approach. The sample consisted of 93 mothers with children under five selected through simple random sampling. Data were collected using questionnaires and observation sheets from June 19 to July 3, 2025. Statistical analyses included Chi-Square and multiple logistic regression tests. The results showed that 33.3% of children were stunted, 34.4% had poor access to health services, and 68.8% lived in unhealthy housing conditions. Bivariate analysis indicated significant relationships between maternal age (p = 0.007), maternal education (p = 0.012), maternal occupation (p = 0.002), access to health services (p = 0.001), family income (p = 0.032), and healthy housing conditions (p = 0.007) with stunting incidence. Multivariate analysis revealed that access to health services was the strongest factor associated with stunting (p = 0.010; OR = 4.294; 95% CI: 1.411–13.06). Children with limited access to health services were 4.3 times more likely to experience stunting. The study recommends improving the accessibility and quality of maternal and child health services and strengthening multisectoral interventions and health education programs to prevent stunting.